Determination of sunitinib and its active metabolite, N‐desethyl sunitinib in mouse plasma and tissues by UPLC‐MS/MS: assay development and application to pharmacokinetic and tissue distribution studies. (8th October 2014) - Chen, Xiao; Wang, Zhong; Liu, Mengping; Liao, Min; Wang, Xinfeng; Du, Huajuan; Chen, Jiefeng; Yao, Meicun; Li, Qing
Abstract A simple, sensitive and specific method using ultraperformance liquid chromatography/tandem mass spectrometry (UPLC‐MS/MS) was developed to determine sunitinib and N‐desethyl sunitinib in mouse plasma and tissues. The analytes were separated by an isocratic mobile phase consisting of acetonitrile and buffer solution (water with 0.1% formic acid and 5 m m ammonium acetate; 40: 60, v/v) running at a flow rate of 0.35 mL/min for 2 min. Quantification was performed using a mass spectrometer by multiple reaction monitoring in positive electrospray ionization mode. The transition was monitored at m/z 399 → 283, m/z 371 → 283 and m/z 327 → 270 for sunitinib, N‐desethyl sunitinib and internal standard, respectively. Calibration curves were linear over concentration ranges of 2–500, 0.5–50 and 1–250 ng/mL for plasma, heart and other biosamples. The method was successfully applied to animal experiments. The pharmacokinetic study indicated that sunitinib was eliminated quickly in mice with a half‐life of 1.2 h; tissue distribution data showed more sunitinib and its metabolite in liver, spleen and lung, which provided reference for further study. Copyright © 2014 John Wiley & Sons, Ltd.